An analytical method for computing the coefficients of the trivariate polynomial approximation - Şafak, Süleyman (My University, 2013)
This paper deals with computing the coefficients of the trivariate polynomial approximation (TPA) of large distinct points given on ?3. The TPA is formulated as a matrix equation using Kronecker and Khatri-Rao products of the matrices. The coefficients of the TPA are computed using the generalized inverse of the matrix. It is seen that the trivariate polynomial approximation can be investigated as the matrix equation and the coefficients of the TPA can be computed directly from the solution of the matrix equation.

Bu makale, ?3 de verilen çok sayıda farklı noktanın üç değişkenli polinom yaklaşımındaki katsayıların hesaplaması ile ilgilidir. Üç değişkenli polinom yaklaşımı, matrislerin Kronecker ve Khatri - Rao çarpımlarını kullanarak bir matris denklemi olarak formüle edilmiştir. Bu polinomun katsayıları bir matrisin genelleştirilmiş tersi kullanılarak hesaplanmıştır. Üç değişkenli polinom yaklaşımın bir matris denklemi olarak incelenebileceği ve bu polinomun katsayılarının doğrudan bu matris denkleminin çözümünden hesaplanabileceği görülmüştür.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Polynomial approximation; Trivariate polynomial; Generalized inverse of a matrix; Matrix equation; Polinom yaklaşımı; Üç değişkenli polinom; Matrisin genelleştirilmiş tersi; Matris denklemi